Toni Morrison's Spiritual Vision : Faith, Folktales, and Feminism in Her Life and Literature - Nittle, Nadra (Book collections on Project MUSE., 2021)
Toni Morrison's Spiritual Vision unpacks an oft-ignored but essential element of her work--her religion--and in so doing gives readers a deeper, richer understanding of her life and her writing. As Nadra Nittle's wide-ranging, deep exploration of Morrison's oeuvre reveals, to fully understand Morrison's work, one must also understand the role of religion and spirituality in her life and literature.